La pureza y la carne: el cuerpo de las mujeres en el imaginario político de la sociedad colonial - Araya Espinoza, Alejandra (Revista de Historia Social y de las Mentalidades, 2011)
The authores incorporates the category body in an exercise of deep refle ction to check the characteristics of the western domination, fixing her look specifically in case of the colonial women. The concept of chastity, which arises from this category of analysis, all ows —as indicates the authoress — to connect the political dilemma of the colonial society, with that of the women in it. The principle of the purity, it allows to elaborate procedure that they must protect to the minority group that tries to legitimize his superiority o pposite to others, procedure that harden respect of those who must be the s ecurity of these limits because they are carnal in essence: the women